Diversity of plasmids harboring blaCMY-2 in multidrug-resistant Escherichia coli isolated from poultry in Brazil - Ferreira, Joseane Cristina (2017)
Multidrug-resistance (MDR) has been increasingly reported in Gram-negative bacteria from the intestinal microbiota, environment and food-producing animals. Resistance plasmids able to harbor different transposable elements are capable to mobilize antimicrobial resistance genes and transfer to other bacterial hosts. Plasmids carrying blaCMY are frequently associated with MDR. The present study assessed the presence of plasmid-encoded ampC genes (blacmy, blamox, blafox, blalat, blaact, blamir, bladha, blamor) in commensal E. coli isolated from apparently healthy broiler chickens. Furthermore, we characterized the plasmids and identified those harboring the resistance genes. We isolated 144/200 (72%) of E. coli isolates with resistance to cefotaxime and the resistance gene identified was blaCMY-2. The pulsed-field gel electrophoresis (PFGE) analysis showed high diversity of the genetic profiles. The phylogenetic groups A, B1, B2, and D were identified among E. coli isolates and group D was the most prevalent. The PCR-based replicon typing (PBRT) analysis identified four distinct plasmid incompatibility groups (Inc) in MDR isolates. Moreover, plasmids harboring blaCMY-2, ranged in size from 50 kb to 150 kb and 51/144 (35%) belonged to IncK, 21/144 (14.5%) to IncB/O, 8/144 (5.5%) to IncA/C, 1/144 (0.5%) to IncI, while 63/144 (44.5%) were not typeable by PBRT. Overall, a high prevalence of blaCMY-2 genes was found in a diverse population of commensal MDR E. coli from poultry in Brazil, harbored into different plasmids.